THE ACCOUNTANT AS AN EFFICIENCY EXPERT. - Drucker, A. P. R. (The Accounting Review, 1928)
Abstract It was in the main due to an accident that the efficiency idea was taken over by the engineering fraternity. The accountants, had they interested themselves in that direction, would have made better efficiency experts than the engineers, for they are by education and training better fitted for efficiency work. In the first place the accountant has a better grasp of business and economics subjects because of his education than has the engineer. Second, the accountant, coming constantly into contact with business men, has a better understanding of human relationships. He can deal better with people, whereas the nature of the engineer's work enables the latter to deal best with machinery and construction problems. An excellent judge of problems connected with bridges, roads, etc., he is more or less at a loss when confronted with problems involving human relationships. The efficiency engineer has tried to handle the workman as though he were a machine. The accountant on the other hand, accustomed as he has to deal tactfully with people, would never have antagonized labor against the whole efficiency movement as has the engineer.